2020
DOI: 10.1055/a-1099-2902
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Allergie – tödliche „Fake News“ in der Krankenakte?

Abstract: ZusammenfassungDie Prävalenz von Penicillin-Allergien in der Krankenakte wird in der Literatur mit 8 – 12% angegeben und stellt die häufigste berichtete „Allergie“ dar. Allerdings wurden nicht verifizierte „Penicillin-Allergien“ in den vergangenen Jahren als ein zunehmendes Public-Health-Problem mit in der Folge ansteigender Dauer der Hospitalisierung, höheren Wiederaufnahmeraten, häufigerem Behandlungsversagen und vermehrten Aufnahmen auf der Intensivstation erkannt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…[22][23][24] Various investigations have explored the precision of a historybased questionnaire for the assessment of antibiotic allergies. [25][26][27] In preoperative contexts, a structured allergy history increased beta-lactam prophylaxis by 277 (57%) cases out of 485 patients, reducing alternative antibiotic use from 81.9% to 55.9%. 28 Similarly, systematic preoperative checklist excluded IgE-mediated reactions in 337 (67%) of 503 self-reported antibiotic allergies and in a multicenter study, a clinical decision rule accurately identified low-risk penicillin allergies with a 96.3% negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Various investigations have explored the precision of a historybased questionnaire for the assessment of antibiotic allergies. [25][26][27] In preoperative contexts, a structured allergy history increased beta-lactam prophylaxis by 277 (57%) cases out of 485 patients, reducing alternative antibiotic use from 81.9% to 55.9%. 28 Similarly, systematic preoperative checklist excluded IgE-mediated reactions in 337 (67%) of 503 self-reported antibiotic allergies and in a multicenter study, a clinical decision rule accurately identified low-risk penicillin allergies with a 96.3% negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Nicht verifizierte "Penicillin-Allergien" wurden in den vergangenen Jahren als ein zunehmendes Public-Health-Problem mit dadurch ansteigender Dauer der Hospitalisierung, höheren Wiederaufnahmeraten, häufigerem Behandlungsversagen und vermehrten Aufnahmen auf der Intensivstation erkannt, wobei eine deutlich erhöhte Exposition gegenüber Antibiotikaklassen, die mit einem erhöhten Risiko für Clostridioides-difficile-Infektionen einhergehen und als Treiber der Resistenzentwicklung für Methicillin-resistente Staphylococcus aureus (MRSA) und multiresistente gramnegative Erreger (MRGN) gelten, beobachtet wurde (Schulz-Stübner 2019).…”
Section: Wie Kann Ich Es Umsetzen?unclassified